Morphological Errors In Narrative Writings Of The Eleventh Students Of Muharrikun Najaah Klaten - Sunandar, Ahmad (CV. Kalimasada Group Profesional, 2023)
This research conducted to investigate the morphological errors in students’ narrative writings. The aim of this study was to categorize and demonstrate the percentage of each error that students made, according to theory. Descriptive qualitative research methods were the chosen research type. The research subjects were the students of Senior High School of Muharrikun Najaah Klaten of the eleventh grade which had two classes with 55 students. The instrument used was the students’ narrative writings. The Surface Strategy Taxonomy developed by Dulay et al. was used to assess each error that emerged in the students’ writings. The findings showed that the total errors were 447. The most errors were the misformation with 175 errors or 39 %, the second place was the omission with 142 errors or 32 % , the third place was the addition with 102 errors or 23 %, and the last place was the misordering with 28 errors or 6 %. Based on the results, it can be concluded that students still made great difficulties in learning the grammar structure. So that the result of the study is significant and expected to be able to raise the awareness of the students about the importance of mastering English structures.